2010
DOI: 10.1152/ajpcell.00417.2008
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β suppresses the upregulation of MMP-2 by vascular smooth muscle cells in response to PDGF-BB

Abstract: During platelet-derived growth factor (PDGF)-BB-mediated recruitment to neovascular sprouts, vascular smooth muscle cells (VSMCs) dedifferentiate from a contractile to a migratory phenotype. This involves the downregulation of contractile markers such as smooth muscle (SM) alpha-actin and the upregulation of promigration genes such as matrix metalloproteinase (MMP)-2. The regulation of MMP-2 in response to PDGF-BB is complex and involves both stimulatory and inhibitory signaling pathways, resulting in a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 78 publications
(99 reference statements)
5
36
0
1
Order By: Relevance
“…Exposure of cultured SMCs to pro-inflammatory molecules like interleukin (IL)-1a, tumour necrosis factor (TNF)-a, and oxidised low-density protein are shown to significantly increase the expression and activity of MT1-MMPs, which further leads to the increased activation of proMMP-2 [43]. However, another study demonstrated that autocrine expression and activation of transforming growth factor (TGF)-b1 antagonises the platelet-derived growth factor (PDGF)-BB (homodimer of PDGF subunit B/beta polypeptide)-induced upregulation of MMP-2 in SMCs during phenotypic modulation [48], suggesting TGF-b1 promotes contractile phenotype by modulating MMPs. Cumulatively, these findings illustrate the differential regulation of MMP expression by different growth factors and cytokines.…”
Section: Expression and Regulation Of Mmps In Vasculature Vascular Cellsmentioning
confidence: 99%
“…Exposure of cultured SMCs to pro-inflammatory molecules like interleukin (IL)-1a, tumour necrosis factor (TNF)-a, and oxidised low-density protein are shown to significantly increase the expression and activity of MT1-MMPs, which further leads to the increased activation of proMMP-2 [43]. However, another study demonstrated that autocrine expression and activation of transforming growth factor (TGF)-b1 antagonises the platelet-derived growth factor (PDGF)-BB (homodimer of PDGF subunit B/beta polypeptide)-induced upregulation of MMP-2 in SMCs during phenotypic modulation [48], suggesting TGF-b1 promotes contractile phenotype by modulating MMPs. Cumulatively, these findings illustrate the differential regulation of MMP expression by different growth factors and cytokines.…”
Section: Expression and Regulation Of Mmps In Vasculature Vascular Cellsmentioning
confidence: 99%
“…In the vessels there is an excessive deposition of calcium, transition of smooth myocytes from media into intima. Elastin of arteries is thinned that is characterized by fragmentation phenomena under the influence of matrix metalloproteinases and transforming growth factorTGFβ [12,13]. In contrast, the collagen protein synthesis is promoted with the assistance of angiotensin II, which increases the rigidity of collagen itself and vascular wall [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, MMPs might negatively regulate cancer cell growth by TGF-β1.For example, MMP-2 expression is suppressed by a threshold level of active TGF-β1, which in turn promotes a contractile vascular smooth muscle cells phenotype that prevents the up-regulation of MMP-2 (Risinger et al, 2010). TGF-β1 modulates the mRNA and protein levels of MMPs (MMP-2 and MMP-9) as much as their inhibitors (TIMP-2 and RECK) (Gomes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%